2021
DOI: 10.1002/htj.22156
|View full text |Cite
|
Sign up to set email alerts
|

Quartic autocatalysis of homogeneous and heterogeneous reactions in the bioconvective flow of radiating micropolar nanofluid between parallel plates

Abstract: This study deals with the quartic autocatalysis of homogeneous–heterogeneous chemical reaction that occurs in the bioconvective flow of micropolar nanofluid between two horizontally parallel plates. The quartic autocatalysis is found to be more effective than cubic autocatalysis since the concentration of the homogeneous species is substantially high. The upper plate is assumed to be in motion and the lower plate is kept stationary. Such a flow of micropolar fluid finds application in the pharmaceutical indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The effects of a Thompson and Troian slip boundary in an SWCNT/MWCNT-water nanofluid flow close to the point of stagnation along an expanding or contracting surface in a Dacry-Forchheimer porous medium combined with quartic autocatalysis chemical reaction was analyzed by Ramzan et al [25]. Additional studies have been referenced in; see [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a Thompson and Troian slip boundary in an SWCNT/MWCNT-water nanofluid flow close to the point of stagnation along an expanding or contracting surface in a Dacry-Forchheimer porous medium combined with quartic autocatalysis chemical reaction was analyzed by Ramzan et al [25]. Additional studies have been referenced in; see [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Koriko et al [ 20 ] analyzed the process of bio-convection comprising the implosion of microorganisms in a thixotropic nanofluid. Puneeth et al [ 21 ] discussed the homogeneous and heterogeneous chemical reactions with the quartic autocatalysis for the flow of micropolar nanofluid flowing in a channel subjected to thermal radiation for microorganism interference. Azam et al [ 22 ] evaluated the impact of nonlinear radiation in the flow of nanofluid under the influence of motile cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Koriko et al 21 analyzed the process of bioconvection thixotropic nanofluid caused by the swimming of motile cells. Puneeth et al 22 discussed the bioconvection process and the quartic autocatalysis chemical reactions in the flow of a micropolar nanofluid in a channel subject to thermal radiation. Azam et al 23 concluded that the radiation enhances the nanofluid temperature in the presence of motile microorganisms.…”
Section: Introductionmentioning
confidence: 99%